Individual, community and maternal care level determinants of stillbirth in Madhesh province, Nepal: a hierarchical logistic regression analysis - Dipendra Kumar Yadav; Prakash Sharma; Jitendra Kumar Singh; Niranjan Shrestha; Arun Kumar Koirala; Ramchandra Sinha; Amar Nagila; Bhoopendra Sharma; Santosh Kumar Gupta; Rajesh Kumar Yadav; Prabin Sharma; Saroj Yadav (International Journal of Public Health Asia Pacific, 2026)
Background: The incidence of stillbirth remains a pressing public health issue, particularly in developing regions where rates persist despite efforts to enhance maternal and neonatal health. Objectives: This study aims to identify risk factors associated with stillbirths in Madhesh Province, Nepal. Methods: Employing a case-control study and using quantitative methods, this study investigated determinants of stillbirth at maternal care service levels in Madhesh Province. The study population comprised mothers who utilized delivery-related services at healthcare facilities and had recorded birth outcomes, either stillbirth or live birth. Data were gathered through surveys and interviews with women who experienced stillbirths. Various analytical models were employed, with integrating pregnancy-related factors to provide a comprehensive understanding of determinants. Results: The analysis revealed significant impacts of husband support during pregnancy (AOR: 8.79, 95% CI: 1.30-59.30), antenatal checkups at government facilities (AOR: 5.53, 95% CI: 1.08-28.31), longer travel times (>30 minutes) to health facilities (AOR: 4.95, 95% CI: 1.05-23.27), and pregnancy complications (AOR: 13.36, 95% CI: 3.03-58.84) on stillbirth outcomes. This model advances understanding by underscoring the role of social and cultural influences in shaping maternal and child health outcomes. Conclusions: The study underscores the critical influence of social and cultural factors as unsupportive husband during pregnancy, inadequate access to government health facilities, facing complications during pregnancy and longer travel time (>30 minutes) to reach health facilities on stillbirth outcomes in Madhesh Province, Nepal. Addressing these determinants through targeted interventions and policies holds promise for improving maternal and neonatal health.